Experimental Analysis of Pre-Forming Parameters on Abnormalities, Thickness, and Void Content of Glass/Epoxy Composite In VBO-Oven Cure Manufacturing - Md Hanafiah, Nur Hafzareen; Othman, Abdul Rahim (Journal of Engineering and Technological Sciences, 2024)
Autoclave-based production of composite laminates leads to extended time requirements, increased manufacturing expenses, and the accumulation of significant residual stress. These limitations have spurred research and innovation in seeking alternative out-of-autoclave (OOA) processing methods. The present study aimed to measure the impact of distinct and combined pre-forming parameters within the pre-forming process of vacuum bagging with oven curing (VBO-oven curing) on thickness, abnormalities, and void content in cured laminates of conventional, cost-effective glass/epoxy autoclave composite material. The abnormalities were analyzed using ultrasonic C-scan and thickness measurement was done to determine thickness variations. A burn-off test was employed to measure the void content. The relationship between processing parameters was subsequently investigated via analysis of variance (ANOVA). Higher thickness standard deviation was yielded at higher abnormality percentages in the C-scan results, resembling total discontinuities and non-uniformities. Voids were highest in the laminate produced via the standard pre-forming process. Edge breather, release wax, and intensifier reduced the void content by approximately 11.87%, 12.93% and 6.85%, respectively.